1995
DOI: 10.1080/03079459508419093
|View full text |Cite
|
Sign up to set email alerts
|

Replication of influenza A viruses of high and low pathogenicity for chickens at different sites in chickens and ducks following intranasal inoculation

Abstract: SUMMARYTen specific pathogen free light breed chickens and 10 commercial layer ducks were inoculated intranasally with one of five avian influenza A viruses which had been characterised as showing high or low pathogenicity for chickens. Recovery of the two viruses of low pathogenicity was restricted to the respiratory tract and gut of both species. Highly pathogenic viruses were recovered from all organs sampled. With two of the highly pathogenic viruses, A/duck/Ireland/113/83 (H5N8) and A/chicken/Victoria/85 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
43
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 17 publications
4
43
1
Order By: Relevance
“…By contrast, older ducks are able to survive infection with the Asian HPAI H5N1 viruses from the clade 2.2 genotype, suggesting that ducks have the ability to control the replication of the most virulent HPAI viruses. Importantly, HPAI viruses have a similar tropism in poultry and ducks, and comparative analyses have revealed that viral titres found in ducks are lower than in chickens (Perkins & Swayne, 2003;Wood et al, 1995). These observations suggest that ducks have developed specific immune mechanisms enabling them to control influenza virus replication efficiently.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…By contrast, older ducks are able to survive infection with the Asian HPAI H5N1 viruses from the clade 2.2 genotype, suggesting that ducks have the ability to control the replication of the most virulent HPAI viruses. Importantly, HPAI viruses have a similar tropism in poultry and ducks, and comparative analyses have revealed that viral titres found in ducks are lower than in chickens (Perkins & Swayne, 2003;Wood et al, 1995). These observations suggest that ducks have developed specific immune mechanisms enabling them to control influenza virus replication efficiently.…”
Section: Introductionmentioning
confidence: 80%
“…Highly pathogenic avian influenza (HPAI) viruses have also been isolated from ducks (De Marco et al, 2005;Sturm-Ramirez et al, 2005). Interestingly, whilst abrupt death is the usual outcome of HPAI virus infection in gallinaceous poultry, HPAI virus-infected ducks usually present only mild clinical signs and recover from infection (Perkins & Swayne, 2003;Wood et al, 1995). Asian HPAI H5N1 viruses from the clade 2.2 genotype represent an exception, as they have been described as being lethal to ducks (Kim et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…No detectable lesions were observed in the kidneys of MZ-or MZ-delNA-inoculated animals, even when the presence of infectious virus was established. Viral replication in the liver and/or kidney has been observed following natural infection or intratracheal inoculation with highly pathogenic avian influenza virus (30,45,75). Like for low-pathogenicity viruses, nephrotropism and nephropathogenicity were observed mostly upon intravenous inoculation in chickens (12,67,68).…”
Section: Discussionmentioning
confidence: 95%
“…As an example of a historical pre-Asianlineage H5N1 HPAIV bearing the typical avian virus signature PB2 627E, we used A/turkey/England/50-92/1991 (50-92) virus, reportedly restricted to Galliformes (43,44 (26,46). The 50-92, Ty/05, and pH1N1 PB1, PB2, PA, and NP genes were subcloned into the pCAGGS expression plasmid as described previously (25,26).…”
mentioning
confidence: 99%